Early Childhood Education Teacher Resilience in Rural Areas: Concept, Improvement Efforts and Urgency - Dede, Dede Hikmah; Wulan, Sri; Yetti, Elindra (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
The success of early childhood education in rural areas cannot be separated from teacher resilience. The research aims to explore scientific insights into the urgency, influencing factors and efforts to increase the resilience of early childhood teachers in rural areas. The study used the Systematic Literature Review method by applying the PRISMA Protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analysis. The results show that early childhood teachers' resilience is needed to support their critical role in providing quality early childhood education amid unique challenges such as limited resources and isolation. Factors that are at the core of teacher resilience include emotion regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and